2005
DOI: 10.1161/circulationaha.104.489310
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Strain Rate Analysis as an Adjunct to Wall-Motion Scoring for Assessment of Myocardial Viability by Dobutamine Echocardiography

Abstract: Background-Assessment of myocardial viability based on wall-motion scoring (WMS) during dobutamine echocardiography (DbE) is difficult and subjective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
1
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(106 citation statements)
references
References 38 publications
5
86
1
14
Order By: Relevance
“…20,21 In our study, the akinetic but viable myocardium of patients with ABS showed more prominent postsystolic shortening. 5,[20][21][22][23][24][25][26] in our study, the systolic and postsystolic shortening parameters were not different between patients with recovered akinetic myocardium and those without recovered akinetic myocardium, and they were not able to predict recovery in patients with AMI with revascularization. Most other studies included not only akinetic but also hypokinetic myocardium.…”
Section: Discussioncontrasting
confidence: 58%
“…20,21 In our study, the akinetic but viable myocardium of patients with ABS showed more prominent postsystolic shortening. 5,[20][21][22][23][24][25][26] in our study, the systolic and postsystolic shortening parameters were not different between patients with recovered akinetic myocardium and those without recovered akinetic myocardium, and they were not able to predict recovery in patients with AMI with revascularization. Most other studies included not only akinetic but also hypokinetic myocardium.…”
Section: Discussioncontrasting
confidence: 58%
“…Strain is a measure of myocardial deformation, which is an intrinsic mechanical property. Myocardial strain derived by tagged magnetic resonance imaging (MRI) (Garot, Lima 2004), by Doppler echocardiography (Hanekom, Jenkins 2005) and by 2DSE (Reisner, Lysyansky 2004) have incremental value to conventional measures of regional myocardial function in ischemic heart disease. Our group recently demonstrated that 2DSE is a sensitive and specific means of detecting myocardial viability and stunning in a rat ischemiareperfusion model, and was superior to regional thickening by 2D and M-mode echocardiography (Migrino, Zhu 2007).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The determination of PEVL by strain rate imaging may be a solution to overcoming the tethering effect and the variability of its value depending on the segments assessed, unlike its parent methodology, TDI. However, although strain rate imaging technique is theoretically a promising and interesting tool, especially thanks to its independence of tethering or translational effect, it is highly susceptible to signal noise and, as such, inter-observer correlation is not satisfactory, [25][26][27] which is an important pragmatic limitation that compromises the clinical acceptance of strain rate imaging technique. Third, the apical segments were omitted from the analyses, which could not be avoided because of the inherent limitation of TDI; that is, angle-dependency.…”
Section: Discussionmentioning
confidence: 99%